Performance Evaluation of 119.88 kWp IoTBased On-Grid Solar System at Admin Building Grissik - Putra, Asri Eka; Hasan, Abu; Bow, Yohandri (EKSAKTA: Journal of Sciences and Data Analysis, 2025)
The global rise in carbon emissions has intensified the urgency of transitioning toward renewable, environmentally friendly and sustainable energy systems, particularly in industrial sectors with high fossil fuel dependency such as oil and gas. Solar panels represent a clean and reliable alternative for electricity generation. This research evaluates the performance of a 119.88 kWp monocrystalline solar panel system integrated with an Internet of Things (IoT)-based on-grid monitoring system at the Grissik Administration Building. Over a 30-day observation period, the solar panels supplied an average of 432 kWh/day, approximately 72.07% of the installed capacity, reducing fuel gas consumption by 0.19 MMSCFD and lowering CO₂ emissions by 10.38 tons. System efficiency exceeded 80% under optimal irradiation conditions. The IoT-based monitoring platform facilitated real-time data and system control, improving operational decision-making and reliability. This research provides novel empirical evidence of field-scale performance of IoT-integrated photovoltaic systems within Indonesia’s oil and gas facilities, demonstrating their significant role in enhancing industrial energy efficiency and supporting the national clean energy transition.